Corrosion Performance of Cu-Based Coins in Artificial Sweat - J. Porcayo-Calderon; R. A. Rodríguez-Díaz; E. Porcayo-Palafox; L. Martinez-Gomez (Journal of Chemistry)
The performance of different Cu-based coins in artificial sweat was evaluated. The electrochemical behavior of the coins was determined by potentiodynamic polarization curves, linear polarization resistance, and electrochemical impedance spectroscopy. Regardless of the chemical composition of the Cu-based coins, they showed similar polarization curves; particularly, the observed similarity in the anodic zone suggests that the corrosion mechanism is the same in all cases. The presence of Ni and Zn does not appreciably affect the corrosion resistance of Cu. However, the presence of both elements affects the corrosion resistance of Cu. Electrochemical impedance spectroscopy measurements showed the presence of three time constants with very similar characteristics, again indicating that the main corrosion mechanism is the same in all cases. Equivalent circuits confirmed that the corrosion performance of the Ni-Zn-Cu coins depends on the Zn/Ni ratio, such that decreasing this value decreases the corrosion resistance of the alloy. In general, nickel has a detrimental effect due to the formation of highly soluble Ni-based corrosion products.